A Case Report of Multiple Cerebral Abscesses Due to Nocardia in the Absence of Pulmonary Disease. Issue 2 (March 2018) - Elliott, Mark; Dixit, Devika
Abstract : Abstract: A 64-year-old woman with Waldenström macroglobulinemia presented with seizures and was found to have multifocal Nocardia farcinica cerebral abscesses. Nocardia species are an uncommon cause of cerebral abscesses that can occur spontaneously via inoculation from the environment, especially in immunocompromised patients, and usually appear with concomitant pulmonary disease. Nocardia infections generally portend a worse prognosis than other organisms causing the same clinical syndrome because they are difficult to treat. Treatment of cerebral Nocardia consists of combination therapy upfront with a sulfonamide and another agent, with long treatment regimens of up to a year. Abstract : Central nervous system (CNS) Nocardial infections carry a significantly higher mortality than other causative organisms. They are recalcitrant infections requiring long treatment courses with double, or even triple, antibiotic coverage. This case report fills a gap in the recent literature regarding CNS Nocardiosis because the authors were unable to culture the organism necessitating empiric therapy for an extended duration, its atypical staining pattern, and absence of pulmonary disease, which is uncommon.